TIGIT Blockade Exerts Synergistic Effects on Microwave Ablation Against Cancer - Chen, Yaping; Huang, Hao; Li, Yuan; Xiao, Wenlu; Liu, Yingting; Chen, Rongzhang; Zhu, Yulan; Zheng, Xiao; Wu, Changping; Chen, Lujun (Frontiers in Immunology, 2022)
Background Combination immunotherapy based on immune checkpoint inhibitors (ICIs) has shown great success in the treatment of many types of cancers and has become the mainstream in the comprehensive treatment of cancers. Ablation in combination with immunotherapy has achieved tremendous efficacy in some preclinical and clinical studies. To date, our team proved that ablation in combination with ICIs was a promising antitumor therapeutic strategy for the liver metastasis of colorectal cancer (CRC). Moreover, we found that the expression of T cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) expression was up-regulated after microwave ablation (MWA), indicating that TIGIT was involved in immunosuppression, and the combination of MWA and TIGIT blockade represented a potential clinical treatment strategy. Methods In the present study, we examined the expression of TIGIT using a preclinical mouse model treated with MWA. Moreover, we evaluated the antitumor functions of MWA alone or in combination with TIGIT blockade by monitoring tumor growth and survival of the mice. Besides, we also detected the numbers of tumor-infiltrating lymphocytes (TILs), and effector molecules of CD8+ T cells using flow cytometry. Finally, we analyzed the single-cell RNA sequencing (scRNA-seq) data from the MWA and MWA plus anti-TIGIT groups. Results The expression of TIGIT in various immune cells was up-regulated after MWA, and the addition of TIGIT blockade to MWA prolonged survival and delayed tumor growth in the MC38 tumor model. Taken together, our findings showed that TIGIT blockade in combination with MWA significantly promoted the expansion and functions of CD8+ TILs and reshaped myeloid cells in the tumor microenvironment (TME) using flow cytometry and scRNA-seq analysis. Conclusions TIGIT blockade in combination with MWA was a novel treatment strategy for the liver metastasis of CRC, and this combination therapy could reprogram the TME toward an antitumor environment.